ASTEP (2005–2015): Ten years of soft error and atmospheric radiation characterization on the Plateau de Bure. Issue 9 (August 2015) - Autran, J.L.; Munteanu, D.; Moindjie, S.; Saoud, T. Saad; Sauze, S.; Gasiot, G.; Roche, P.
Abstract: This paper surveys ten years of experimentation conducted on the Altitude SEE (Single Event Effects) Test European Platform (ASTEP), a permanent mountain laboratory opened in 2005 on the Plateau de Bure (Dévoluy, France) at the altitude of 2552 m and primarily dedicated to the characterization of soft errors in electronic circuits subjected to terrestrial cosmic rays. The paper retraces the foundations of the project and gives an extensive overview of the different past, current and future experiments conducted on ASTEP in the fields of SER (soft error rate) real-time testing and natural radiation monitoring and metrology. Highlights: The paper retraces the foundations of the ASTEP project. It surveys ten years of real-time soft error rate experimentation conducted on ASTEP. It gives an extensive overview of the different past, current and future experiments.